The Role of Diagnostic Radiology in Pregnancy Induced Gynecological Complications. A Clinical Based Comparative Study - Zubair Janan Orakzai, Sumaira Noureen, Rubia Ahmad, Aaish Naveed, Irsa Ul Rehman, Sara Zainab, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Our clinical expedition sought to unearth the efficacy of diagnostic radiology in unveiling the shrouded dimensions of pregnancy-related gynecological complications, thereby guiding clinicians through the mazes of maternal-fetal well-being. Study Design: In this kaleidoscopic investigation, we orchestrated a prospective, comparative study, meticulously juxtaposing the performance of diagnostic radiology modalities in a cohort of expectant mothers embroiled in the throes of gynecological complications. Study Place and Duration: This study was MTI Mardan Teaching Institute, Mardan Medical Complex Mardan, KPK in the period from January 1, 2022 to December 31, 2022. Methods: 300 pregnant women with complex gynecological issues were selected with great care to participate in the research. Utilizing ultrasound, magnetic resonance imaging, and computed tomography, radiological results were meticulously evaluated, their efficacy was quantified and compared with clinical outcomes, and the mother-child symphony was brought into harmony. Results: In this clinical magnum opus, diagnostic radiology emerged as a guiding beacon, its ultrasonographic prowess unequivocally outshining alternative modalities in unraveling the enigmatic strands of pregnancy-induced gynecological complications (sensitivity: 92.7%, specificity: 89.6%). The harmony of maternal-fetal well-being was upheld, with minimal risks of radiation exposure, and a symphony of optimized clinical decision-making ensued. Conclusion: Our clinical epic concludes that diagnostic radiology, with ultrasonography as its resplendent hero, is an indispensable instrument in navigating the tumultuous seas of pregnancy-induced gynecological complications. This radiant beacon illuminates the path to a harmonious maternal-fetal duet, empowering clinicians to orchestrate a symphony of optimal patient care. Keywords: diagnostic radiology, pregnancy-induced, gynecological complications, ultrasonography, clinical comparative study, maternal-fetal well-being.